The Acquisition of Pragmatically Constrained Japanese Pronouns by L1 English Learners: Results from a Context Translation Task - Carlos Luis Pimentel (Journal of Japanese Language Education and Linguistics, 2024)
The allocation of explicit and implicit pronouns and the literature extensively discusses the syntactic and pragmatic conditions that permit and necessitate the use of overt and null pronouns in Romance languages, such as Spanish and Italian. This topic has been explored by various researchers, including Alonso-Ovalle and D’Introno (2000), Fernández-Soriano (1989), Luján (1987, 1999), Montalbetti (1984), Rigau (1986, 1988), and Rizzi (1997). Rothman (2009) argues that the employment of overt subject pronouns in Spanish is pragmatically unusual, except in select discursive situations when their existence contributes more to semantic interpretation than just agreement features. In Japanese, null forms of pronouns are more common than overt pronouns, as observed by Martin (1976). However, like Spanish, the distribution of pronouns in Japanese is influenced by both syntax and pragmatics. In pro-drop languages, overt pronouns, as well as lexical subjects, have the role of resolving any potential uncertainties that may occur when new referents are introduced in a conversation.